2017
DOI: 10.1002/2017wr020754
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Physically‐Based Flow Simulations of Alluvial Systems Through Atmospheric Noble Gases and the Novel 37Ar Tracer Method

Abstract: To provide a sound understanding of the sources, pathways, and residence times of groundwater water in alluvial river‐aquifer systems, a combined multitracer and modeling experiment was carried out in an important alluvial drinking water wellfield in Switzerland. 222Rn, 3H/3He, atmospheric noble gases, and the novel 37Ar‐method were used to quantify residence times and mixing ratios of water from different sources. With a half‐life of 35.1 days, 37Ar allowed to successfully close a critical observational time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 88 publications
3
78
0
1
Order By: Relevance
“…HGS has been used for the simulation of many different hydrological systems, for example, for the interactions between GW, SW and vegetation (e.g., Ala‐aho et al, ; Banks et al, ; Schilling et al, ; Schomburg et al, ), for the detection of the sensitivity of catchment scale dynamics to the different model parameters (Cornelissen et al, ), to track catchment scale SW levels and overland flow routing (Ameli & Creed, ), to explore the hydrological dynamics of wetlands (Liu et al, ) and microtopographic wetland runoff (Frei et al, ), and for large‐scale solute transport (Blessent et al, ). In a few instances HGS was calibrated against different types of data (e.g., Brunner et al, ; Karan et al, ; Schilling et al, ; Schilling, Gerber, et al, ) using the automatic inverse code PEST (Doherty, ). Recently, HGS has been coupled to a sequential DA routine (EnKF‐HGS) by Kurtz et al ().…”
Section: Methodsmentioning
confidence: 99%
“…HGS has been used for the simulation of many different hydrological systems, for example, for the interactions between GW, SW and vegetation (e.g., Ala‐aho et al, ; Banks et al, ; Schilling et al, ; Schomburg et al, ), for the detection of the sensitivity of catchment scale dynamics to the different model parameters (Cornelissen et al, ), to track catchment scale SW levels and overland flow routing (Ameli & Creed, ), to explore the hydrological dynamics of wetlands (Liu et al, ) and microtopographic wetland runoff (Frei et al, ), and for large‐scale solute transport (Blessent et al, ). In a few instances HGS was calibrated against different types of data (e.g., Brunner et al, ; Karan et al, ; Schilling et al, ; Schilling, Gerber, et al, ) using the automatic inverse code PEST (Doherty, ). Recently, HGS has been coupled to a sequential DA routine (EnKF‐HGS) by Kurtz et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Investigations on the interactions between groundwater, surface water, and vegetation (e.g., Ala‐Aho et al [], Schilling et al [], Schomburg et al []), on the development of unsaturated zones between rivers and aquifers in heterogeneous systems (e.g., Irvine et al [], Schilling et al [], Tang et al []), or on contaminant transport and tile drainage in agricultural contexts (e.g., Bonton et al [], De Schepper et al []) are just some recent examples for which HGS was used. HGS has recently been coupled to the Weather Research and Forecast (WRF) model for the integrated simulation of atmosphere, surface, and subsurface interactions (Davison et al ), to particle tracking and flow tracking tools (Partington et al ; Partington et al ; Chow et al ; Schilling et al ), and to the ensemble Kalman filter (EnKF) data assimilation tool (Kurtz et al ; Tang et al ; Tang et al ).…”
Section: Winter Hydrological Processes In Hgsmentioning
confidence: 99%
“…The modified tilted‐V catchment with alluvial drinking water production is a typical setup in mountainous and peri‐alpine catchments, where winter processes play a key role (Kurtz et al ; Schilling et al ). If winter processes are not taken into account when managing groundwater pumping stations in such systems, during the winter season groundwater abstraction may exceed sustainable amounts because recharge is strongly reduced by the retention of precipitation as snow.…”
Section: Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hydrogeological models require not only more detailed data about aquifer geometry and properties, but also enough suitable data for calibration of unknown parameters. Especially for the USZ and the mixing of different water masses in the SZ, a calibration based on groundwater heads might not be sufficient, and additional tracer data or measurements from the USZ might be necessary for robust results (Schilling et al, 2017;Visser et al, 2009). Furthermore, Eberts et al (2012) showed that if analogous conceptual models are used, LPMs and hydrogeological models often result in very similar contaminant predictions.…”
Section: Reliability and Suitability Of The Modelmentioning
confidence: 99%